Introduction of monitoring activities at the main-canal level: a study of the Kirindi Oya right bank main canal - Maha 1991/92 - Rey, J.; Hemakumara, M.; Mohanrajah, S.; Junaid, M.H. (International Irrigation Management Institute, 1993)
The research activity described in this working paper is a joint effort undertaken by the International Irrigation Management Institute (IIMI) and the Irrigation Department of Sri Lanka. Two of the authors, S. Mohanrajah (Resident Engineer, Irrigation Department) and M. H. Junaid (Additional Engineer, Irrigation Department), were responsible for the management of the Right Bank Main Canal (RBMC) in Kirindi Oya during the season, maha 1991/92. The monitoring network introduced under their supervision, with the active collaboration of the field staff, proved to be of significant benefit for the effective accomplishment of their day-to-day tasks of canal management. This led the authors to the conclusion that disseminating this experience even at an early stage could be of some interest to others seeking the improvement of the management of manually operated irrigation canals. Emphasis has deliberately been put on methods rather than on thorough, a posteriori analysis of data. Thus, ideas suggesting how to use simple flow data to compute indicators and derive management information has been preferred to the in-depth analysis of the data. The authors also hope to convey their intimate conviction of the usefulness of real collaborative action-research between "outside catalysts" and managers in charge of irrigation systems through this paper.